Mitochondria inter-organelle relationships in cancer protein aggregation - Genovese, Ilaria; Fornetti, Ersilia; Ruocco, Giancarlo (Frontiers in Cell and Developmental Biology, 2022)
Mitochondria are physically associated to other organelles, such as ER and lysosomes, forming a complex network that is crucial for cell homeostasis regulation. Inter-organelles relationships are finely regulated by both tether systems, which maintain physical proximity, and by signalling cues that induce the exchange of molecular information to regulate metabolism, Ca2+ homeostasis, redox state, nutrient availability and proteostasis. The coordinated action of the organelles is engaged in the cellular integrated stress response. In any case, pathological conditions alter the functional communication and efficient rescue pathways activation, leading to cell distress exacerbation and eventually to cell death. Among these detrimental signals, misfolded protein accumulation and aggregation represent a major damage for the cells, since defects in protein clearance systems worsen the cell toxicity. A cause for protein aggregation is often a defective mitochondrial redox balance, as also ER freshly translated misfolded proteins and/or deficient lysosome-mediated clearance system. All these features aggravate mitochondrial damage and enhance proteotoxic stress. This review aims to gather the current knowledge about the complex liaison between mitochondria, ER and lysosomes in facing proteotoxic stress and protein aggregation, highlighting both causes and consequences. Particularly, specific focus will be pointed to cancer, a pathology where inter-organelles relations in protein aggregation have been poorly investigated.